(3bUjOI PGJ GdfNHs - (3Ydj Hf GdeZQHjs
(3ChdgG (B:s
(3Ci OHOHg JOHRdi CfG dYi GdeZQHi fGOHi hjMc ai Mb CejQ GdCOH s
(3BNQgG (B:s
(3hGdQZH Edi Gddg aeG CadM ef de jQZH hGgOi SdGekG OGFekG Ydi GdfHi GdYQHi hBdg hUMHg GdZQ GdcQGe GdfLH hdg Yai Gddg Yfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg aGFOIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs